Year-round micrometeorological data from the habitats of terrestrial photosynthetic organisms in Langhovde, East Antarctica, during 2013 - Kosugi, Makiko; Kurosawa, Norio; Kawamata, Akinori; Kudoh, Sakae; Imura, Satoshi (2015)
Fig. 1 ~ 9 | http://polaris.nipr.ac.jp/~parc/pub/v008/nipr_parc_187_0008_2013.doc Raw data 1 | http://polaris.nipr.ac.jp/~parc/pub/v009/nipr_parc_187_0009_2013.xls Raw data 2 | http://polaris.nipr.ac.jp/~parc/pub/v010/nipr_parc_187_0010_2013.xls Movie 1 | http://polaris.nipr.ac.jp/~parc/pub/v011/nipr_parc_187_0011_2013.wmv Table 1 | http://polaris.nipr.ac.jp/~parc/pub/v001/nipr_parc_187_0001_2013.xls Table 2 | http://polaris.nipr.ac.jp/~parc/pub/v002/nipr_parc_187_0002_2013.xls Table 3 | http://polaris.nipr.ac.jp/~parc/pub/v003/nipr_parc_187_0003_2013.xls Table 4 | http://polaris.nipr.ac.jp/~parc/pub/v004/nipr_parc_187_0004_2013.xls Table 5 | http://polaris.nipr.ac.jp/~parc/pub/v005/nipr_parc_187_0005_2013.xls Table 6 | http://polaris.nipr.ac.jp/~parc/pub/v006/nipr_parc_187_0006_2013.xls Table 7 | http://polaris.nipr.ac.jp/~parc/pub/v007/nipr_parc_187_0007_2013.xls departmental bulletin paper